Customer Satisfaction: A Central Phenomenon in Digital Marketing J&T Express - Violinda, Qristin; Alfadila, Annisa; Wattegama, Erandi Jinadari; Gultom, Henry Casandra (Journal of Digital Marketing and Halal Industry, 2022)
The decrease in the number of J&T express users for 2017-2020 is a serious problem because consumers choose to use other expeditions.This study aims to determine the effect of service quality, delivery rates, timeliness on customer satisfaction J&T Express Students of the Faculty of Economics and Business, PGRI University Semarang. In this study, students of the Faculty of Economics and Business, PGRI University Semarang in the 2017,2018,2019 class with a total of 256 respondents. The process of collecting data by distributing questionnaires through the Google Form for Students of the Faculty of Economics and Business, Universitas PGRI Semarang in the 20172018,2019 class. This study uses Multiple Linear Test with IBM SPSS 22. The results of this study indicate a positive and significant effect between service quality, shipping rates on customer satisfaction J&T Express Students of the Faculty of Economics and Business, PGRI University Semarang. Punctuality has no effect on customer satisfaction J&T Express Students of the Faculty of Economics and Business, PGRI University Semarang. Quality of service, delivery rates and timeliness there are variables that must be considered, namely related to timeliness because service quality and delivery rates affect customer satisfaction